Real Election Count Application; Case Study: The 2nd Round Padang Election 2014 - Azandra, Erien Nada; Renato, Erick (Jurnal Sains dan Informatika, 2015)
The author has conducted research in Padang Commission with the aim of knowing the addition of the current system to make it more optiomal future. In this study the authors use the method of Field Research is to conduct research directly into the field, in this case the authors plunge into Citizens and Agencies KPU Alone. From the results of the data collected, then the author uses Research laboratory methods that process the results of the research data in a computer laboratory. made the development of the information generated from the old system and there is the workings of the system itself by utilizing the computer as a means of replacing the tools and software used in data processing. This design is expected sistemyang authors can replace the old system, in order to achieve the level of effectiveness and efficiency higher. so that the design can be useful for the Commission Padang to obtain accurate results.